Ergodic secrecy capacity for downlink multiuser networks using switch‐and‐examine combining with post‐selection scheduling scheme. Issue 9 (11th April 2016) - Yang, Maoqiang; Zhang, Bangning; Huang, Yuzhen; Guo, Daoxing; Yi, Xu
Abstract : A novel threshold‐based scheduling scheme for multiuser downlink wiretap networks is addressed, which consist of a base station (BS), multiple legitimate users and multiple eavesdroppers. Particularly, the active scenario is concentrated, where BS has access to the channel state information for the eavesdropper's channel. In doing so, new exact and asymptotic closed‐form expressions for the ergodic secrecy capacity are derived for multiuser downlink networks using switch‐and‐examine combining with post‐selection scheduling at legitimate users and maximum ratio combining at the eavesdroppers. Moreover, the high signal‐to‐noise ratio slope and power offset are also given to explicitly characterise the impact of main link and wiretap link on the ergodic secrecy capacity. Simulation results show the effect of key parameters such as the number of legitimate users and eavesdroppers, switching threshold on the secrecy performance of the considered wiretap network.